Survey on the tourist satisfaction of rural homestay based on the theory of importance–performance analysis - Zhou, Xiaorui; Wang, Yanan; Ma, Pingping (Frontiers in Psychology, 2022)
Guilin rural homestays are an important support for rural tourism destinations, serving not only as accommodation but also as a representative of the local culture of the town. To improve satisfaction with rural homestays among tourists, enhance destination attractiveness, and better meet tourist demands for accommodation conditions, this study combines literature and network text analysis to construct an evaluation index system for Guilin rural homestay tourist satisfaction. The data collected by a questionnaire survey based on importance–performance analysis (IPA) are analyzed. The results show that actual tourist satisfaction with the experience in the 21 indexes is lower than the pre-consumption expectation, due to the imperfect facilities, lack of special service development, relative optimization of basic road construction, and the need for improvement in the internal and external environment, among other factors. Through the improvement of the above factors, the satisfaction of tourists to the rural homestay can be improved.